2011
DOI: 10.1007/s10827-011-0354-8
|View full text |Cite
|
Sign up to set email alerts
|

After-hyperpolarization currents and acetylcholine control sigmoid transfer functions in a spiking cortical model

Abstract: Recurrent networks are ubiquitous in the brain, where they enable a diverse set of transformations during perception, cognition, emotion, and action. It has been known since the 1970's how, in rate-based recurrent on-center off-surround networks, the choice of feedback signal function can control the transformation of input patterns into activity patterns that are stored in short term memory. A sigmoid signal function may, in particular, control a quenching threshold below which inputs are suppressed as noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 138 publications
(214 reference statements)
0
22
0
Order By: Relevance
“…For instance, the membrane potential recovery from afterhyperpolarization in MEC layer II stellate cells is known to be quickened in proportion to the action of I h [83]. Also, the fast and slow-medium currents that determine AHP in stellate cells [84] may have potentially different effects [85]. Moreover, the role of the persistent sodium (NaP) current, whose interplay with I h is known to generate subthreshold MPOs [86], is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the membrane potential recovery from afterhyperpolarization in MEC layer II stellate cells is known to be quickened in proportion to the action of I h [83]. Also, the fast and slow-medium currents that determine AHP in stellate cells [84] may have potentially different effects [85]. Moreover, the role of the persistent sodium (NaP) current, whose interplay with I h is known to generate subthreshold MPOs [86], is not fully clear.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, in vivo observations that cholinergic neurons in MS, compared to GABAergic neurons, have low firing rates that vary on slow time scales of several tens of seconds (Zhang et al, 2010) are not inconsistent with this conclusion, because grid cell recordings ensued 5 min after the start of lidocaine infusions into MS for the Koenig et al (2011) study, and 2 min after the start of muscimol infusions into MS for the Brandon et al (2011) study. Ongoing modeling is starting to characterize how ACh-dependent modulations of various ion channels, notably slow, medium, and fast AHP currents, can influence biophysical properties of individual spiking neurons (Palma et al, 2012b) and networks of such neurons (Palma et al, 2012a). Such studies may in the future be applied to a spiking network model of grid cells (Pilly and Grossberg, 2013) to more completely analyze the disruptive effects on grid cells of silencing the MS.…”
Section: Discussionmentioning
confidence: 99%
“…However, as demonstrated in Palma et al (2011), a more realistic approximation uses a mass action law, similar to other kinetic models (Destexhe et al, 1994a,b), to introduce an intermediate variable. This is expressed by two differential equations: dRdt=(1R)IRτr, and dgSDdt=(τf+τrτf)[2τr(1gSD)RgSDτf]…”
Section: Methodsmentioning
confidence: 99%
“…The Palma et al (2011) analysis revealed simple rules that govern conductance changes in the three AHP currents as they combine to generate desired changes in signaling. It was shown that, for spiking neurons, a leftward threshold shift occurs when the sAHP and mAHP currents decrease, while the fAHP current increases.…”
Section: Introductionmentioning
confidence: 99%